The Effect of Atmosphere Store, Customers Relationship Management on Loyalty through Customer Satisfaction - Buana, Chandra; Maftukhah, Ida (Management Analysis Journal, 2019)
This study aims to examine the direct indirect influence of store atmosphere, customer relationship management, and customer satisfaction as an intervening variable on customer loyalty. The population this research is Loffle Pop Up Dessert visitor in Semarang. Sampling technique using purposive sampling questionnaire. Data analysis using descriptive percentage and path analysis. The results show that store atmosphere does affect customer loyalty, customer relationship management affect customer loyalty and customer satisfaction influence cutomer loyalty and mediate the influence of store atmosphere and customer relationship management on customer loyalty.